Backcountry Avalanche Safety : a Guide to Managing Avalanche Risk - 4th Edition - Daffern, Tony (RMB Rocky Mountain Books, 2017)
Essential reading for all outdoor enthusiasts who venture into mountainous terrain where avalanches are common.In spite of the increasing sophistication of avalanche hazard forecasting, an alarming number of people die every year in backcountry avalanche accidents. This updated edition of Backcountry Avalanche Safety contains the latest information on avalanche risk and focuses on the following vital topics:• Mountain Weather• Snow and Snowpack• Types of Avalanches• Avalanche Terrain• Trip Planning• Avalanche Gear• Travel in Avalanche Terrain• Riding Steep Slopes• Companion RescueUsing colour photographs along with detailed charts, graphs and diagrams, the author clearly explains the importance of managing risk while enjoying backcountry adventure during the winter months.